NICER detection of 9.29 s pulsations from RX J0209.6-7427 - Iwakiri, W.; Wolff, M. T.; Vasilopoulos, G.; Gendreau, K.; Arzoumanian, Z.; Markwardt, C.; Strohmayer, T. E.; Ray, P. S.; Altamirano, D.; Mihara, T.; Negoro, H.; Guillot, S.; et al. (2019)
MAXI J0206-749 is a hard X-ray transient detected by MAXI/GSC (ATel #13300) in the direction of the Small Magellanic Cloud (SMC) wing. Follow-up Swift/XRT observations (ATel #13303) identified MAXI J0206-749 with the HMXB RX J0209.6-7427.
Keywords: Pulsar; Transient